Suzuki Method in the training prospective specialists in preschool education - Yankovych, Oleksandra Ivanivna (Journal of Education, Health and Sport, 2020)
The article presents the results of the research on the use of the Suzuki Method and the technology of forming musical and creative abilities of preschool children in the People’s Republic ofChinaby means of the Suzuki Method (author Sun Jingqiu) in training prospective kindergarten teachers at higher education institutions ofUkraine. Promising ways of using this technology in educational process have been revealed: its comprehensive analysis during studying pedagogical and music-pedagogical subjects; the use of the Suzuki Method as a component of the technology “Organization of successful activities”.